Exploring the Impact of Music on English Language Acquisition Among Alpha Generation: A Descriptive Qualitative Study - Venny Tawaffani Muslimah; Wahyu Satya Gumelar; Riki Ruswandi (Universitas Islam Negeri Palopo, 2025)
This research investigates the influence of music on English language learning among Generation Alpha students at SMP IT Sains Albiruni in Bandung, Indonesia. Data were gathered using semi-structured interviews and questionnaires from five participants chosen through purposive sampling, utilizing a qualitative case study methodology. According to Automaticity Theory (LaBerge & Samuels, 1974; DeKeyser, 2001), the results indicate that 94% of students perceive vocabulary retention as more manageable when facilitated by music, whereas 100% acknowledge enhanced pronunciation. Furthermore, 89% of participants assert that music improves their enthusiasm to acquire English. Music-based learning promotes student engagement with authentic language input and enhances listening comprehension abilities. The research indicates that incorporating music-based techniques into language education improves engagement, language proficiency, and motivation among Generation Alpha students.